The need for 'good clinical practice' in health care research - Robson, N.Z.M.H.; Aziz, N.; Aziz, A.F.A.; Hamid, M.Z.A.; Mohamed, M.; Othman, S.; Hussein, N. (Scopus, 2009)
Randomised controlled trials form the foundation for ‘evidence-based-medicine’, but the results of such research can be relied upon only if it was conducted according to principles and standards collectively referred to as ‘Good Clinical Practice’ (GCP). The GCP was established as a basis both for the scientific and ethical integrity of research involving human subjects and for generating valid observations and sound documentation of research findings. It provides a framework for clinical investigators and pharmaceutical companies to conduct clinical trials according to similar rules and regulations, to ensure clinical research is consistently performed to high ethical and scientific standards and an assurance that the data and reported results are credible and accurate, and that the rights, integrity, and confidentiality of trial subjects are protected. Thus the GCP protects the rights, safety and well-being of subjects and ensures that investigations are scientifically sound and advance public health goals.